Chapter Two Second Order Ordinary Differential Equation (SOODE)
Chapter Two Second Order Ordinary Differential Equation (SOODE)
Chapter Two Second Order Ordinary Differential Equation (SOODE)
CHAPTER TWO
Second Order Ordinary Differential
Equation(SOODE)
Remark: Super position principle in general doesn’t hold for non-homogeneous and non-
linear.
Example
1
Dagnachew J.
Example:
√ √
1. Show that the set of functions, f1 (x) = x + 5, f2 (x) = x + 5x, f3 (x) = x − 1 and
f4 (x) = x2 is linearly dependent on (0, ∞)
Solution:
2
Dagnachew J.
2. Show that the set of functions, sin2 (x), cos2 (x), sec2 (x) and tan2 (x) is linearly depen-
dent on (− π2 , π2 )
Solution: (Tutorial)
Exercise:
Theorem 2. Let y1 and y2 be any two linearly independent solutions of y 00 +p(x)y 0 +f (x)y =
0. If y3 = y3 (x) is any other solutions of y 00 + p(x)y 0 + f (x)y = 0 , then there are constants
α1 and α2 such that y3 (x) = α1 y1 (x) + α2 y2 (x)
⇒ y = α1 y 1 + α2 y 2
is a general solution.
3
Dagnachew J.
R
⇐⇒ ln |z|R + 2 ln |y1 | = − p(x)dx ⇐⇒ zy12 = e− p(x)dx
R
− p(x)dx
or z = e y2 = u0 = du dx
R1 e− R p(x)dx R e− R p(x)dx
Thus u = y12 dx and y2 (x) = y1 (x). y12
dx is the solution of (1) which is linearly
independent with y1 .
Example:
x2 y 00 + 2xy 0 − 2y = 0
Differential Operator
dy
Let D stands for the operator dx d
i.e., D = dx d
. Then Dy = dx = y 0 and (D − C)y =
d dy
( dx − C)y = dx − Cy where C is a constant.
d d2 d3
Note: dx , dx2 , dx3 , ... etc denoted by D, D2 , D3 , ... respectively.
Remark: Two operators A and B are equal if and only if Ay = By for all functions y
The linear DE of the nth order with constant coefficient:
dn y dn−1 y dn−2 y dy
cn dx n + cn−1 dx
n−1
+ c n−2 dxn−2 + ... + c1 dx + c0 y = r(x)......(∗)
4
Dagnachew J.
n −a o e 2
−a −a −a
x x x
Hence e , xe 2 2 is fss and y(x) = c1 e 2 + c2 xe 2 x is the general solution.
5
Dagnachew J.
Example:
1. Solve y 00 + 4y 0 + 4y = 0
Solution: Lecture
Solution:(Tutorial)
Case(3):a2 − 4b < 0
The characteristic
√
equation
√
has complex solutions: √
−a+ a2 −4b −a+ 4b−a2 i 4b−a2
m1,2 = 2
= 2
=⇒ m = m1,2 = α+βi, where α = − a2 and β = 2
Note: From Eulers formula:
eiθ = cos(θ) + i sin(θ), θ ∈ < and e−iθ = cos θ − i sin θ then
e(α+βi)x = eαx (cos(βx) + i sin(βx)) = y1 (x)
and e(α−βi)x = eαx (cos(βx) − i sin(βx)) = y2 (x)
y1∗ (x) = (y1 +y
2
2)
= eαx cos(βx)
y2∗ (x) = − 12 i(y1 − y2 ) = eαx sin(βx)
Therefore {y1∗ (x), y2∗ (x)} = {eαx cos(βx), eαx sin(βx)} is fss.
Hence y = eαx (c1 cos(βx) + c2 sin(βx)) is general solution.
Example:
1. Solve y 00 − 2y 0 + 10y = 0
Solution:
CE: m2 − 2m + 10 = 0
CR: m1 = 1 + 3i, m2 = 1 − 3i
this implies α = 1, β = 3
y = ex (c1 cos(3x) + c2 sin(3x))
2. Consider two concentric spheres of radius r = a and r = b, a < b.The temperature u(r)
in the region between the spheres is determined from the boundary-value problem
d2 u du
r 2
+2 = 0 , u(a) = u0 , u(b) = u1
dr dr
where u0 and u1 are constants.Solve for u(r).
Solution: (Tutorial)
Exercise: Solve
00
2y + 9y 0 − 5y = 0
1. y(0) = 2
y 0 (0) = 1
2. y 00 + 5y 0 + 6y = 0
6
Dagnachew J.
3. y 00 = 0
4. y 00 − 2y 0 − 5y = 0
5. 3y 00 + y 0 − 10y = 0.
Function Annihilator
xm−1 Dm
eαx D−α
cos(βx) D2 + β 2
sin(βx) D2 + β 2
xm−1 eαx (D − α)m
xm − 1 cos(βx) (D2 + β 2 )m
xm−1 sin(βx) (D2 + β 2 )m
eαx cos(βx) D2 − 2αD + (α2 + β 2 )
eαx sin(βx) D2 − 2αD + (α2 + β 2 )
xm−1 eαx cos(βx) (D2 − 2αD + (α2 + β 2 ))m
xm−1 eαx sin(βx) (D2 − 2αD + (α2 + β 2 ))m
2
Note: It is difficult to find the annihilator for the functions like ex , log(x), tan(x).
7
Dagnachew J.
Solution: (Tutorial)
Exercise: Solve the following Differential Equation using the methods of undetermined
coefficient
8
Dagnachew J.
1) y 00 − y 0 − 12y = e4x
2) y 00 + 25y = 6sinx
3) y 00 + 6y 0 + 9y = −xe4x
4)y 00 − 2y 0 + 5y = ex sinx
Solving f (D)y = r(x) Using Variation of Parameters(VP)
Let a set {y1 , y2 } be a fss of f (D)y = r(x).
The complementary solution of f (D)y = r(x) is yc = c1 y1 (x) + c2 y2 (x), c1 = c2 = constants
To determine yp vary the constant c1 and c2 to functions of x,i.e.,
yp (x) = c1 (x)y1 (x) + c2 (x)y2 (x) where c1 (x), c2 (x) are functions of x.
Then yp0 = c01 (x)y1 (x) + c1 (x)y10 (x) + c02 (x)y2 (x) + c2 (x)y20 (x)
←→ yp00 (x) = c001 (x)y10 (x) + 2c01 (x)y10 (x) + c1 (x)y100 (x) + c002 (x)y2 (x) + 2c02 (x)y2 (x) + c2 (x)y200 (x)
Substituting in (1): c001 y10 + 2c01 y10 + c1 y100 + c002 y2 + 2c02 y20 + c2 y200 + p(x)(c01 y1 + c1 y10 + c02 y2 +
c2 y200 ) + f (x)(c1 y1 + c2 y2 ) = r(x)
←→ c001 y1 +2c01 y10 + c002 y2 +2c02 y20 + p(x)(c01 y1 + c02 y2 )+ c1 (y100 + p(x)y10 + f (x)y1 )+ c2 (y200 + p(x)y20 +
f (x)y2 ) = r(x)
←→ (c001 y1 + c01 y10 + c002 y2 + c02 y20 ) + (c01 y10 + c02 y20 ) + p(x)(c01 y1 + c02 y2 ) = r(x)
←→ (c01 y1 + c02 y2 )0 + (c01 y10 + c02 y20 ) + p(x)(c01 y1 + c02 y2 ) = r(x)
Choose c1 (x) and c2 (x) so that c01 y1 + c02 y2 = 0, then c01 y10 + c02 y20 = r(x)
c1 y1 + c02 y2 = 0
0
Solve
c01 y10 + c02 y20 = r(x)
y1 y2
Since W (x) = 0 = y1 y20 − y10 y2 6= 0
y1 y20
From Cramer’s
rule c01(x) and c02 (x) are
uniquely
determined
0 y2
y
1
0
r(x) y20 (x)
0
y1 r(x)
c01 (x) = W (x)
and c 0
2 (x) = W (x)
(y2 (x))(r(x))
0
←→ c1 (x) = − (y2 (x))(r(x))
R
Then c1 (x) = − W (x) dx
0 (y1 (x))(r(x)) R y1 (x)r(x) W (x)
and c2 (x) = W (x)
←→ c2 (x) = W (x)
dx
Therefore yp (x) = c1 (x)y1 (x) + c2 (x)y2 (x)
Hence y = yc + yp is the general solution.
Example:
1. Solve y 00 − 2y 0 + y = x12 ex , x > 0 using VP.
Solution:y 00 − 2y 0 + y = x12 ex
Hom.form: y 00 − 2y 0 + y = 0
CE: m2 − 2m + m = 0
CR: m = 1(double.)
yc (x) = c1 ex + c2 xex
To find yp we vary c1 and c2 as a function of x.
i.e.,yp = c1 (x)ex + c2 (x)xex
Sincey1 (x) = ex ←→ y10 (x) = ex and y2 (x) = xex ←→ y20 (x) = ex + xex
0 0
c1 (x)y1 (x) + c2 (x)y2 (x) = 0 c01 (x)ex + c02 (x)xex = 0
Now ←→
c01 (x)y10 (x) + c02 (x)y20 (x) = r(x) c01 (x)ex + c02 (x)ex (1 + x) = x12 ex
9
Dagnachew J.
ty 00 − (t + 1)y 0 + y = t2
given that
y1 (t) = et , y2 (t) = t + 1
Solution: (Tutorial)
Exercise:
00 Solve the following using VP.
y + 4y = sec(2x)
a) y(0) = 1
y 0 (0) = 2
b) y 00 − 2y 0 + y = ex ln(x), x > 0.
2. The system is said to be linear if the unknown functions and their derivatives involve
in each equations only to the first power.
Note:
1. Each equation has at least one derivative.
10
Dagnachew J.
dy
dt
= −4x − 2(x − dx dt
+ 23 t2 ) + 4t + 1 = −6x + 2 dx
dt
− 3t2 + 4t + 1 substituting this equation
in to (∗ ∗ ∗) we get a second order linear equation:
d2 x
dt2
+ dx
dt
− 6x = 3t2 − 4t − 1 ⇐⇒ x = c1 e2t + c2 e−3t − 21 t2 is the general solution and if we
substitute this in to equation (∗) we get the other solution, i.e.,
y = − dxdt
+ x + 32 t2 = −c1 e2t + 4c2 e−3t + t2 + t
Therefore the solution of the system is
x = c1 e2t + c2 e−3t − 21 t2
y = −c1 e2t + 4c2 e−3t + t2 + t
Exercise: Solve
dx
dt
= 4x − y
1. dy
dt
= 2x + y
dx
dt
= x + 2y + t − 1
2. dy
dt
= 3x + 2y − 5t − 2
11